2008
DOI: 10.1057/jibs.2008.90
|View full text |Cite
|
Sign up to set email alerts
|

Offshore outsourcing as a source of international competitiveness for SMEs

Abstract: Scholars typically view offshore outsourcing as a means of reducing the cost of manufacturing activities for large corporations, yet offshore outsourcing may entail administrative and technical services, and may include activities outsourced by small and medium-sized enterprises (SMEs). Drawing on research in international entrepreneurship and services, we hypothesize and find evidence that offshore outsourcing of administrative and technical services by SMEs is associated with greater extent and scope of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(217 citation statements)
references
References 64 publications
9
199
0
9
Order By: Relevance
“…It may even be said that the findings of our work could complement findings from Di Gregorio et al (2009), which showed that in a sample of 100 small and medium-sized enterprises in the US, outsourcing abroad (especially in the area of technical and administrative services) increases export performance. Still, they suggest, but do not prove, that offshore outsourcing may not be beneficial for large multinational companies, and that the effects depend on the heterogeneity of these firms.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It may even be said that the findings of our work could complement findings from Di Gregorio et al (2009), which showed that in a sample of 100 small and medium-sized enterprises in the US, outsourcing abroad (especially in the area of technical and administrative services) increases export performance. Still, they suggest, but do not prove, that offshore outsourcing may not be beneficial for large multinational companies, and that the effects depend on the heterogeneity of these firms.…”
Section: Discussionsupporting
confidence: 67%
“…At the company level, many empirical studies have examined the factors that determine a firm's export performance (Doh, Bunyaratavej & Hahn, 2009), but few have researched offshore outsourcing as one of these factors (Mol et al, 2005;Di Gregorio, Musteen & Thomas, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Bien que les logiques de ces entreprises soient différentes en raison des spécificités inhérentes à ce type de structure telles que le rôle majeur du dirigeant (Cabrol et Favre-Bonté, 2011 ;Marchesnay et Messeghem, 2011 ;Felicio et Caldeirnha, 2012) et l'importance de la proximité (Torres, 2004 ;Julien, 2002), cette stratégie leur permet, à l'instar des grandes entreprises, d'améliorer leur compétitivité en réduisant les coûts et en se rapprochant de clients internationaux (Di Gregorio, Musteen et Thomas, 2009). …”
Section: Généralement Synonyme De Fermetures D'usines Et De Licenciemunclassified
“…Only 22% of the outsourcing outcomes were negative. Outsourcing has been found to reduce costs [11,12], increase exports [11,13], improve productivity and enhance an organization's flexibility [14] and increase new product innovation [11].…”
Section: Why Outsource?mentioning
confidence: 99%